Strengthening private certification systems through public regulation: The case of sustainable public procurement. Issue 1 (11th February 2014) - D'Hollander, David; Marx, Axel
Abstract : Purpose: – Private certification systems (PCS) have emerged as governance tools for sustainable development, regulating social and environmental standards through global supply chains. PCS are seen as essentially private and market-driven, but governments have engaged with them in various ways. There are also substantial differences in the institutional design of PCS with regard to the standard-setting process, ex-ante conformity assessment and ex-post verification procedures. Consequently, what determines the institutional design of PCS has attracted growing attention. This article argues that governments, through public regulation, influence the design of PCS, which in turn affects their effectiveness. The paper aims to discuss these issues. Design/methodology/approach: – First, a review of academic literature, policy and legal documents presents how PCS have become institutionalized in government policy, focusing on sustainable public procurement (SPP) regulation. Second, the authors explore the link between effectiveness and the institutional design of PCS by empirically assessing the variations between institutional parameters conducive to effectiveness. Data from the Ecolabel Index database were used to assess the presence or absence of four institutional design parameters related to the rule-making and monitoring mechanisms of PCS. Findings: – Public procurement regulations are important drivers influencing the institutional design of PCS. The buying power and market share of government spending is a potential tool for policy-makers not only to stimulate the adoption of PCS, but also for shaping their design and effectiveness. However, the impact of such policies is highly dependent upon the market-share of public procurement within a given sector. In addition to public procurement frameworks, other factors drive the institutional evolution of PCS. Originality/value: – The article connects two themes within the study of non-state market regulation; the growing interaction of governments with PCS, and the institutional variety and development of these systems.